PKM PENINGKATAN NILAI TAMBAH LIMBAH KULIT KOPI PADA KELOMPOK WANITA TANI DI KAWASAN WISATA KINTAMANI, BANGLI-BALI - Mayun Wirajaya; Made Sri Yuliartini; I Gusti Bagus Udayana (Universitas Warmadewa, 2021)
Belantih Village, which is located in the western part of the Kintamani tourist area with beautiful scenery and landscapes and fertile soil, is a dominant center for producing horticultural products, coffee and citrus plantations. Most of the people of Belantih Village still rely on working in the agricultural sector as their main source of income. Taking advantage of the development of tourism, farmers can fill tourism needs by cultivating plants properly. Until now, in Belantih Village, the most developed plants are beans, tomatoes, cabbage, eggplant, chilies covering 11.13 ha, while for citrus fruits it is 175 ha and coffee plants are 282 ha. To support the growth and development of plants in addition to using inorganic fertilizers, most farmers still use organic fertilizers derived from cow and chicken manure which are easily available in large quantities and can meet the needs of a fairly large planting area from outside the Belantih Village area. Until now, the source of organic fertilizer that can actually be utilized from coffee rind waste from the rest of the wet processing or other processing from factories around Belantih Village is still not processed further in order to improve the quality of the waste as a source of fertilizer. This opportunity can actually be used by women farmer groups as an opportunity to supply organic fertilizer from solid coffee husk waste. The nutrient content contained in coffee husk waste when given a touch of technology will be a source of nutrients for plants. The purpose of this PKM activity is to increase the knowledge and skills of partners in coffee cultivation and after post-harvest the use of coffee husk waste as organic fertilizer in substituting the use of inorganic fertilizers in partner areas. In addition, it can be an alternative that solid coffee husk waste for communities around partners can be used as organic fertilizer in fertilizing cultivated plants in addition to organic fertilizers from cows and chickens that have been used today. The touch of technology in the processing of coffee skin waste is expected to add value to the fertilizer produced. Activities are carried out with counseling, discussions, direct practice in the field. This PKM program was carried out in a women's farmer group